Reading and writing short fiction in the university classroom mediated by the Padlet collaborative tool - Hermosillo Núñez, Perla Cristal (IE Revista de Investigación Educativa de la REDIECH, 2024)
This paper presents an analysis of the reading and writing practices carried out through the Padlet collaborative tool, through short fiction as a textual and literary genre, by the fifth-semester group of the bachelor’s degree in Education of the Centro Universitario de los Valles of the Universidad de Guadalajara, Jalisco, Mexico. It consists of a qualitative study with theoretical support on discovery learning. The information was collected through semi-structured interviews and the analysis of Padlets prepared during the 2022-B school year (August-December). The main findings are that textual genres and prototypes, as well as their modeling, affect how students read and write at university to communicate their knowledge, learning, and ways of collaborating and contributing to group dynamics. The most relevant conclusions focus on the fact that the mediation of digital platforms, such as Padlet, is a fundamental aspect of the study of reading and writing at university, considering virtual literacy environments in combination with face-to-face activities and interaction, since they contribute to the establishment of various forms of interaction, collaboration, and communication between students and teachers.